Removal of Chromium(Vi), Copper(Ii) and Arsenic(V) from Aqueous Solution and Wastewater by Ethylenediamine Modified Rice Hull - Tang, Poh Li (2002)

(untitled)
The potential of aminated rice hull to remove Cr(VI), Cu(II) and As(V) from aqueous solution was investigated. Amination processes enhanced the sorption capacities of rice hull with ethylenediamine being the most economical and efficient aminating agent. Chemical modification of surface functional groups of ethylenediamine modified rice hull (enRH) indicated that amine and carboxyl groups were the major sorption sites. Both batch and column studies were performed, taking into account parameters such as pH, contact time, initial concentrations, ionic strength, particle size of sorbent, rate of agitation, presence of competitive cation and anions, use of different metal ion sources, sorbent dosage, temperature, bed depth, flow rate and sorptiondesorption process. The results of batch studies indicated that the sorption process was pH and temperature dependent. External mass transfer was not the sole rate-limiting phase and might involve chemisorption. The sorption of metal ions from single metal ion solution was in the order of Cr(VI) > Cu(II) > As(V) which is consistent with the Pearson's theory on hard and soft acid base. Cr(VI) and As(V) sorptions involved electrostatic interactions while Cu(n) sorption involved complexation. Where Cu(n) was present in binary and ternary metal ion solutions, Cr(VI) and As(V) removal also involved complexation. Column studies revealed different equilibrium states compared with batch studies. Breakthrough was bed depth, flow rate and initial concentration dependent. The presence of sulfate significantly affected the breakthrough time of Cr(VI) and Cu(n). The relationship between service time and bed depth was linear. The predicted breakthrough curves obtained from a two-parameter mathematical model agreed well with the experimental values in Cu(II) from all systems and Cr(VI) from binary Cu(II)- Cr(VI) and ternary metal ion solutions when sulfate was absent. Sequential columns could successfully reduce the levels of Cr(VI) and Cu(II) in the wastewater to the allowable limit for discharge into inland water. Cr(VI) and Cu(II) from dilute solution could be preconcentrated on the enRH column and thus this is useful in the analysis of trace amounts of Cr(VI) and Cu(II) in wastewater. Elution ofCr(VI)- and Cu(II)-loaded column could be carried out using 1.07 M NH3 and 0.5 M H2S04, respectively.